FACTORS INFLUENCING PURCHASE INTENTION TOWARDS GROUP ORDER FEATURE IN ONLINE FOOD DELIVERY PLATFORM IN INDONESIA - Stella Kurniawan (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
Online Food Delivery in Indonesia shows growing trends for the past years. Group Order feature help to eliminate customer pain points when ordering food together, such as complicated ordering process, splitting the bill, and tracking the order which make this feature become popular in the workplace and community. This feature has become one of the sales boosting trends of Online Food Delivery platforms. Prior studies have mostly examined Online Food Delivery platforms, and recent study have started to explore Group Order feature. This study examines social influence, promotions, customer attitude, and purchase intention towards Group Order feature, especially in Indonesia. This research developed 7 hypotheses with each hypothesis test variable relationship and mediation. This research was conducted in quantitative by online questionnaire with 229 respondents. The data analyzed using descriptive analysis, PLS-SEM, hypothesis testing, and mediation analysis. This study shows that customer attitudes have the strongest relationship and largest effect size towards purchase intention. Social influence and promotion have a positive relationship towards customer attitude and purchase intention. From these research findings, promotion needs to prioritize building customer attitude rather than direct purchase intention. This research helps to explore Group Order features in Online Food Delivery platforms, especially in Indonesia.